Efficient processing of RDF documents with directed hypergraphs. - Martínez-Morales, Amadís Antonio; Vidal, María Esther (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
Resource Description Framework (RDF) is a proposal of the WWW Consortium (W3C) to express metadata about resources in the Web. The RDF data model has been formalized using different graph-based representations, each one with its own limitations with respect to expressive power and sup-port for the tasks of query answering and semantic reasoning. In this paper, we show the advantages of the directed hypergraph-based representation for RDF documents, and analyze space complexity required to store an RDF document, and the impact of this representation on the time complexity of the query answering task. In addition, we empirically compare the DH approach with respect to the labeled directed graphs and bipartite graphs representations. Experimental results show that the time/space tradeoff of the DH-based representation outperforms the other two approaches.